Analisis Kebutuhan Perencanaan Sistem Informasi Manajemen Partograf Berbasis Web Di Puskesmas Pajang Surakarta - SARI, Fevi Fitria (2015)
Partograph serve as an instrument that is used to monitor childbirth. In childbirth upbringing the use of partograph is one of whose competence owned the midwife. The use of partograph at puskesmas pajang has not run well. It was because the partograph too much that is stuffed and too small script and partograph used are form manual. The purpose of this research is analyzing planning needs partograph web-based. This is descriptive research by adopting both qualitative. Data collection techniques using interviews, focus group discassions and study documentation. The results of the study indicated the weakness of partograph manual situated on the overhead and point existing partograph. In functional requirements the concept of functional used in planning partograph web based use partograph manually and there is the world of more in terms of a display as well as the output. Non functional requirements include facilities and infrastructures that affect the process will be designed according to the needs of midwives while the output is still shaped partograph but in terms of look like the system.